Fenomenologis Moderasi Beragama pada Madrasah di Aceh - Imran Muhammad (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Today, in understanding, the millennial generation has appeared to deviate from the concept of moderation, as evidenced by the emergence of terror from millennials. Today's millennials are trapped in religious ideology which has the potential to damage the peace and harmony of the nation and state. The adherents of this ideology are easy to recognize, among the criteria that appear and can be seen immediately are in terms of attitude, such as feeling themselves the holiest, most righteous, apart from those who are heretics, heretics, and even disbelievers. This study tries to describe the phenomena that occur and the efforts of madrasas in Aceh in fostering students not to be trapped in religious phenomena that undermine the peace of the nation and state. The results of the study show that these radical or extremist actors indoctrinate millennials with an understanding that is contrary to the government's attitude towards the diversity of religious communities or stereotypes towards Religious Moderation. besides that through the use of information technology such as social media by creating content that leads to rejection of government policies, especially regarding religious moderation. The efforts of madrasas in Aceh in fostering students are through habituation of spiritual attitudes and character development in extracurricular activities.